Knowledge of Hand Hygiene among Health Care Workers of Jigme Dorji Wangchuck National Referral Hospital, Thimphu, Bhutan - Lhamo , Chhimi; Bajgai , Gyan Prasad (Research Highlights in Disease and Health Research Vol. 8, 2023)
This chapter aimed to assess the compliance and the level of knowledge of the health care workers (HCWs) on Proper hand hygiene (HH) at the apex health center in Bhutan. The healthcare-associated infections are the most frequent threat to patient safety globally. This study included 565 HCWs employed at Jigme Dorji Wangchuck National Referral Hospital (JDWNRH). The level of HH knowledge was assessed using self-administered structured questionnaires, while HH compliance was assessed through observation using WHO standardized checklists. The knowledge of HH was assessed from a total of 565 participants (nurses, 57.7%; technicians/technologists, 17.3%; doctors, 10.3%; and support personnel, 9.2%), and 1102 opportunities were observed to assess 380 people' compliance with HH (response rate, 68.34%). Of the total 1102 observations, 20.5% performed HH by application of alcohol-based hand rub, 12.9% used soap and water, while 66.6% missed or did not perform HH; HH compliance rate stood at 33.5%. 76% of the participants possessed a moderate to low level of knowledge about HH; overall knowledge about HH was at a moderate level (M = 7.31, SD = 1.95). In this study population, the overall HH compliance rate was determined to be below average. This study's findings about low compliance rates and a lack of understanding of HH practices are alarming, and they highlight the need to strengthen HH practices at all levels.